The role of long non-coding RNAs and circular RNAs in cervical cancer: modulating miRNA function - Heidari-Ezzati, Sama; Moeinian, Parisa; Ahmadian-Nejad, Bahar; Maghbbouli, Faezeh; Abbasi, Sheida; Zahedi, Mahlagha; Afkhami, Hamed; Shadab, Alireza; Sajedi, Nayereh (Frontiers in Cell and Developmental Biology, 2024)
Cervical cancer (CC) is a primary global health concern, ranking as the fourth leading cause of cancer-related death in women. Despite advancements in prognosis, long-term outcomes remained poor. Beyond HPV, cofactors like dietary deficiencies, immunosuppression, hormonal contraceptives, co-infections, and genetic variations are involved in CC progression. The pathogenesis of various diseases, including cancer, has brought to light the critical regulatory roles of microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). The aberrant expression of these miRNAs, lncRNAs, and circRNAs plays a pivotal role in the initiation and progression of CC. This review provides a comprehensive summary of the recent literature regarding the involvement of lncRNAs and circRNAs in modulating miRNA functions in cervical neoplasia and metastasis. Studies have shown that lncRNAs and circRNAs hold great potential as therapeutic agents and innovative biomarkers in CC. However, more clinical research is needed to advance our understanding of the therapeutic benefits of circRNAs and lncRNAs in CC.